Factors Influencing the Evolution of Pulmonary Hypertension in Previously Healthy Subjects Recovering from a SARS-CoV-2 Infection - Tudoran, Cristina; Tudoran, Mariana; Lazureanu, Voichita Elena; Marinescu, Adelina Raluca; Cut, Talida Georgiana; Oancea, Cristian; Pescariu, Silvius Alexandru; Pop, Gheorghe Nicusor (Journal of clinical medicine, 2021)
(1) Background: While the COVID-19 pandemic has been persisting for almost 2 years, more and more people are diagnosed with residual complications such as pulmonary hypertension (PH) and right ventricular dysfunction (RVD). This study aims to evaluate the course of PH and borderline PH (BPH) at 3 and 6 months after the acute COVID-19 infection and investigate if there are differences regarding its evolution between the patients from the first three waves of this disease. (2) Methods: We analyzed, by transthoracic echocardiography (TTE), the 3 and 6 months’ evolution of the echocardiographically estimated systolic pulmonary artery pressures (esPAP) in 116 patients already diagnosed with PH or BPH due to COVID-19 during the first three subsequent waves of COVID-19. (3) Results: We documented a gradual, statistically significant reduction in esPAP values, but also an improvement of the parameters characterizing RVD after 3 and 6 months (p < 0.001). This evolution was somewhat different between subjects infected with different viral strains and was related to the initial severity of the pulmonary injury and PH (adjusted R2 = 0.722, p < 0.001). (4) Conclusions: PH and RVD alleviate gradually during the recovery after COVID-19, but in some cases, they persist, suggesting the activation of pathophysiological mechanisms responsible for the self-propagation of PH.